2022
DOI: 10.1086/719009
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Hypocrisy and Out-Group Threat: Explaining Citizen Support for Democratic Erosion

Abstract: With widespread democratic backsliding globally, people's support for democracyeroding leaders is receiving overdue attention. But existing studies have a difficulty disentangling contextual effects (such as who is in power at the time of the survey) from individual differences (like which party one supports and how strongly). Moreover, we lack evidence on the causal antecedents of these attitudes. We propose a novel survey experimental design to strip away the political context through hypothetical scenarios,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 14 publications
5
63
0
Order By: Relevance
“…The argument is different from yet consistent with the classical accounts described above as well as extant explanations of why voters support undemocratic political leaders (e.g., Graham and Svolik 2020;Frederiksen 2022aFrederiksen , 2022bCarey et al 2020;Touchton et al 2020;Bartels 2020;Albertus and Grossman 2021;Ahlquist et al 2018;Svolik 2020;Luo and Przeworski 2019;Braley et al 2021;Carey et al 2019;Simonovits et al 2022;Cohen et al 2022). For example, Linz (1978, 72) observed that defection in presidential systems-which should not be equated but surely overlaps with two-party systems-is costly due to a 'winner-takes-all'-logic.…”
Section: Theoretical Argumentmentioning
confidence: 66%
“…The argument is different from yet consistent with the classical accounts described above as well as extant explanations of why voters support undemocratic political leaders (e.g., Graham and Svolik 2020;Frederiksen 2022aFrederiksen , 2022bCarey et al 2020;Touchton et al 2020;Bartels 2020;Albertus and Grossman 2021;Ahlquist et al 2018;Svolik 2020;Luo and Przeworski 2019;Braley et al 2021;Carey et al 2019;Simonovits et al 2022;Cohen et al 2022). For example, Linz (1978, 72) observed that defection in presidential systems-which should not be equated but surely overlaps with two-party systems-is costly due to a 'winner-takes-all'-logic.…”
Section: Theoretical Argumentmentioning
confidence: 66%
“…Further sobering findings emerge from a new experimental paradigm to study voting behavior (Graham and Svolik, 2020), which confronts respondents with the choice between two hypothetical candidates for political office with randomly varied attributes on traits, issue orientations, or violations of democratic norms. The common finding of this new body of research is that large majorities of citizens tolerate violations of a democratic norm if they receive policy payoffs in return (Carey et al, 2022;Saikkonen and Christensen, 2022;Simonovits et al, 2022). These studies led observers to conclude that "only about 3.5 Percent of Americans care about democracy" (Wood, 2020).…”
Section: Introduction: the Puzzling Behavior Of Ordinary Citizensmentioning
confidence: 99%
“…Partisan allegiance selectively influences blame attribution (Bisgaard 2019), drives social media engagement (Rathje et al 2021;Yu et al 2021;Osmundsen et al 2021;Brady et al 2017), shapes perceptions of hostile rhetoric (Muddiman 2017;Mutz 2015;Stevens et al 2015), and influences willingness to censor political opponents (Amira et al 2021;Ashokkumar et al 2020;Lelkes and Westwood 2016). Some evidence even suggests that partisans prioritize partisanship over democracy (Graham and Svolik 2020;Frederiksen 2022;Simonovits et al 2022;Svolik 2018), dehumanize members of the opposing party (Martherus et al 2021;Moore-Berg et al 2020), and increasingly condone political violence if the other side wins (Kalmoe and Mason 2022). Based on this, coming to terms on hate speech restrictions seems like an infeasible task.…”
Section: Introductionmentioning
confidence: 99%